Peningkatan Karakter Melalui Bahan Ajar Sejarah Kebudayaan Islam Berbasis Deep Dialog and Critical Tingking Siswa Madrasah Tsanawiyah - Alfauzan Amin; Alimni Alimni (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
English: This research aims to develop Islamic Culture History teaching materials based on deep dialogue and critical thinking (DD&CT), which are valid, practical, and effective for madrasah tsanawiyah students. This type of research is research in the framework of R & D (Research and Development), which aims to produce or develop a product, especially teaching material products. The research subjects for testing the products developed in the study were seventh-grade students of Bengkulu City Madrasah Tsanawiyah MTs N 2 Kepahyang and MTsN2 Rejang Curup in the 2020/2021 academic year. This study's variables are independent, dependent, and control variables. This research procedure prepares SKI teaching materials through the following stages: (a) Preliminary study by conducting interviews with students and teachers. Syllabus analysis studies and analyzes basic competencies in the preparation of teaching materials. (b) Collecting learning resources, literature, and the main points of material to be compiled. (c) Preparation of draft SKI teaching materials. (d) Limited trial of the product. (e) Product wider trial. (f) Data processing and evaluation. This research concludes by developing teaching materials for SKI subjects, namely materials developed from the 2013 curriculum, syllabus, and lesson plans. The feasibility of SKI teaching materials is validated and assessed by expert judgment from content feasibility, presentation focus, language focus, graphic focus, media visualization focus, and SKI teaching materials.Indonesia: Tujuan penelitian ini ialah menghasilkan pengembangan bahan ajar Sejarah Kebudayaan Islam berbasis deep dialogue and critical thinking (DD&CT) yang valid, praktis dan efektif bagi siswa madrasah tsanawiyah. Jenis penelitian ini adalah riset dalam rangka R&D (Research and Development) yang bertujuan untuk menghasilkan atau mengembangkan suatu produk terutama produk bahan ajar. Subjek penelitian untuk uji coba produk yang dikembangkan dalam penelitian adalah siswa kelas VII Madrassah Tsanawiyah Kota Bengkulu MTs N 2 Kepahyang dan MTsN2 Rejang Curup Tahun Ajaran 2020/2021. Variabel dalam penelitian ini adalah variabel bebas, variabel terikat, dan varibel control. Prosedur penelitian ini adalah proses penyusunan bahan ajar SKI melalui tahap-tahap sebagai berikut: (a) Studi pendahuluan, dengan melakukan wawancara terhadap peserta didik dan guru. Studi analisis silabus dan menganalisa kompetensi dasar dalam penyusunan bahan ajar (b) Mengumpulkan sumber belajar dan literatur serta pokok-pokok materi yang akan disusun. (c) Penyusunan draft bahan ajar SKI. (d) Uji coba terbatas produk. (e) Uji coba lebih luas produk. (f) Pengolahan data dan evaluasi. Kesimpulan penelitian ini adalah pengembangan bahan ajar mata pelajaran SKI yaitu bahan dikembangkan dari kurikulum 2013, silabus dan RPP. Kelayakan bahan ajar SKI divalidasi dan dinilai oleh expert judgement dari aspek kelayakan isi, fokus penyajian, fokus bahasa, fokus kegrafikan, dan fakus visualisasi media dan bahan ajar SKI.